Effect of Grape Pomace Polyphenols With or Without Pectin on TMAO Serum Levels Assessed by LC/MS-Based Assay: A Preliminary Clinical Study on Overweight/Obese Subjects - Annunziata, Giuseppe; Maisto, Maria; Schisano, Connie; Ciampaglia, Roberto; Narciso, Viviana; Hassan, Sherif T. S.; Tenore, Gian Carlo; Novellino, Ettore (Frontiers in Pharmacology, 2019)
Growing evidence suggests that trimethylamine N-oxide (TMAO) is recognized as a biomarker of increased cardiovascular risk. So far, the evaluation of TMAO serum levels in the clinical practice is limited due to the lack of developing new facile methods with reduced limitations. However, few approaches were achieved to determine TMAO in serum by using mass spectrometry-based technique, some limitations were reported including the use of internal standards. Therefore, in this work, a liquid chromatography-mass spectrometry (LC/MS) based-assay was developed to evaluate the effect of grape pomace extract (Taurisolo®, group A) or Taurisolo®+pectin (group B) on TMAO serum levels in a cohort of overweight/obese subjects. The serum levels of TMAO have been assessed before and after treatment, through LC/MS analysis. After 8-week treatment, in both intervention groups TMAO serum levels significantly decreased (-78.58% p = 0.006 and -76.76% p = 0.001, group A and group B, respectively). Moreover, we performed several analyses aimed to validate the LC/MS method we used. The method has high precision (%CV = from 12.12% to 3.92% and from 8.25% to 1.07 % for intraday and interday, respectively) and accuracy (%bias = from -5.52% to 0.5% and from -1.42% to 3.08% for intraday and interday, respectively). TMAO recoveries from serum ranged from 99% to 97%; LOD: 2 ng/ml and LOQ: 6 ng/ml. In conclusion, we demonstrated the efficacy of a novel nutraceutical formulation in reducing TMAO serum levels in high cardiovascular risk-subjects, and proposed a useful, versatile and rapid LC/MS method for identification and quantization of TMAO, without the use of marked/isotopic internal standards. It, thus, may represent a novel and practical method with applications in clinical practice and nutraceutical research. This study is listed on the ISRCTN registry with ID ISRCTN10794277 (doi: 10.1186/ISRCTN10794277).